Carrying capacity, carnivoran richness and hominin survival in Europe. Issue 118 (May 2018) - Rodríguez, Jesús; Mateos, Ana
Abstract: Carrying capacity, the maximum biomass that an ecosystem can sustain over the long term, strongly influences several ecological processes and it is also one of the main determinants of biodiversity. Here, we estimate the carrying capacity (CC) of the late Early and early Middle Pleistocene ecosystems of Europe, using equations describing the relationship between CC and climatic variables observed in the present, as well as maps of inferred paleotemperature and paleoprecipitation. Maps of paleoclimate values were interpolated from the composite benthic stable oxygen isotope ratios and a transfer function was used to estimate ungulate carrying capacity (CCU ) from the interpolated mean annual temperature and annual precipitation values. Carnivoran carrying capacity was subsequently estimated from ungulate carrying capacity and the effect of CC on the carnivoran faunas was analyzed in 12 paleocommunities from Southern Europe. Our results show that carnivoran species richness is strongly related to ungulate carrying capacity in recent ecosystems, but the late Early Pleistocene paleocommunities from Southern Europe included much richer carnivore guilds than would be expected for a recent community with a similar ungulate carrying capacity. Thus, those late Early Pleistocene ecosystems supported a high number of carnivoran species, but the carnivoran biomass they could support was relatively low. Consequently, carnivorans occurred at low densities in Southern Europe compared to the recent African savanna ecosystems, but likely also compared to coeval East African ecosystems. Consequently, the first Homo populations that arrived in Europe at the end of the late Early Pleistocene found mammal communities consisting of a low number of prey species, which accounted for a moderate herbivore biomass, as well as a diverse but not very abundant carnivore guild. This relatively low carnivoran density implies that the hominin-carnivore encounter rate was lower in the European ecosystems than in the coeval East African environments, suggesting that an opportunistic omnivorous hominin would have benefited from a reduced interference from the carnivore guild.